Heptamolybdate: a highly active sulfide oxygenation catalyst12. Issue 34 (29th May 2018) - Porter, Ashlin G.; Hu, Hanfeng; Liu, Xuemei; Raghavan, Adharsh; Adhikari, Sarju; Hall, Derrick R.; Thompson, Dylan J.; Liu, Bin; Xia, Yu; Ren, Tong
Abstract : [Mo2 O11 ] 2− identified as the active species in H2 O2 oxygenation of sulfides catalyzed by heptamolybdate using in situ nano-ESI MS analysis. Abstract : The sulfide oxygenation activities of both heptamolybdate ([Mo7 O24 ] 6−, [1 ] 6− ) and its peroxo adduct [Mo7 O22 (O2 )2 ] 6− ([2 ] 6− ) were examined in this contribution. [Mo7 O22 (O2 )2 ] 6− was prepared in a yield of 65% from (NH4 )6 [Mo7 O24 ] (1a ) upon treatment of 10 equiv. of H2 O2 and structurally identified through single crystal X-ray diffraction study. ( n Bu4 N)6 [Mo7 O22 (O2 )2 ] (2b ) is an efficient catalyst for the sequential oxygenation of methyl phenyl sulfide (MPS) by H2 O2 to the corresponding sulfoxide and subsequently sulfone with a 100% utility of H2 O2 . Surprisingly, ( n Bu4 N)6 [Mo7 O24 ] (1b ) is a significantly faster catalyst than2b for MPS oxygenation under identical conditions. The pseudo-first order k cat constants from initial rate kinetics are 54 M −1 s −1 and 19 M −1 s −1 for1b and2b, respectively. Electrospray ionization mass spectrometry (ESI-MS) investigation of1b under the catalytic reaction conditions revealed that [Mo2 O11 ] 2− is likely the main active species in sulfide oxygenation by H2 O2 .